EFFECT OF STREAMING BY GENDER ON STUDENTS ACHIEVEMENT IN ENGLISH GRAMMATICAL STRUCTURES IN SENIOR SECONDARY SCHOOLS: A CASE STUDY OF OREDO LOCAL GOVERNMENT AREA OF EDO STATE - Danner, R. B. (Sokoto Educational Review, 2020)
This study examines the effect of streaming by gender (school type) and instructional methods and its interaction effect on achievement in English grammatical structures. Four hundred and two (402) SS II students from nine intact classes in six secondary schools in Oredo Local Government Area of Edo State were involved in the study. Three of these nine classes were assigned to each of the treatment and control groups - deductive: inductive and integrative methods. All the 402 Subjects were administered the p re and posttests. The results indicated that achievement scores of students in English grammatical structures are influenced by method of instruction, with the integrative method being the most effective of the three methods. It also revealed that streaming by gender did not significantly affect students’ achievement in English grammatical structures. There was similarly, no method by streaming by gender interaction effect.